Preparation method and application of nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots

The carbon quantum dots prepared by nitrogen-phosphorus-silicon co-doping synthesis method solve the problems of poor flame retardant effects and poor binding force with fiber substrates in the application of existing carbon quantum dots in the field of flame retardant, achieving efficient flame retardant performance and good binding effect.

CN119529831AActive Publication Date: 2025-02-28DEZHOU UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411799632.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

In the application of existing carbon quantum dots in the field of flame retardant, the flame retardant effect is not ideal and the bonding force with the fiber substrate is poor, resulting in the problem of shedding in practical applications.

Method used

Using the synthesis method of nitrogen-phosphorus-silicon co-doped carbon quantum dots with excellent fluorescence and flame retardant properties, the nitrogen-phosphorus-silicon co-doped carbon quantum dots were prepared, and the treatment was sprayed and UV light irradiated to make them closely bound to the fiber substrate.

Benefits of technology

It has achieved effective application of carbon quantum dots in the flame retardant field and fiber field, improved its binding force with fiber substrate, maintained good fluorescence and flame retardant properties, and had small losses in flame retardant properties after washing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529831A_ABST
    Figure CN119529831A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of inorganic flame-retardant materials, and particularly relates to a preparation method and application of nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots. The nitrogen-silicon co-doped carbon quantum dots are prepared by adding a carbon source compound, a nitrogen source compound and a silanization reagent in the hydrothermal synthesis process, meanwhile, the surfaces of the carbon quantum dots contain rich amino groups, one hydrogen atom in the amino groups is substituted by a phosphorus source compound spiro phosphate diacyl chloride, and the nitrogen-silicon co-doped carbon quantum dots are obtained. According to the nitrogen-phosphorus-silicon co-doped carbon quantum dot, nitrogen, phosphorus and silicon elements can improve the fluorescence yield and the flame retardant property of the carbon quantum dot. Moreover, the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dot prepared by the method has a spiral ring structure on the surface, is sprayed on the surface of a fabric in a post-finishing form, is subjected to ring-opening crosslinking under the action of a photoinitiator and UV light, and can be effectively combined with a fiber base material, so that the problem of falling in the subsequent washing and using processes is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of inorganic flame retardant materials, in particular to a preparation method of nitrogen-phosphorus-silicon co-doped flame retardant fluorescent carbon quantum dots and application thereof. Background Art

[0002] In recent years, with the frequent occurrence of fire accidents and the gradual improvement of people's awareness of fire prevention, the development of polymer materials and fiber products with flame retardant properties has become a hot research field. However, traditional flame retardants containing halogens (bromide and chloride), phosphorus and nitrogen often have some problems, such as toxicity, environmental pollution and bioaccumulation, so there is an urgent need to develop more environmentally friendly and efficient flame retardant materials.

[0003] Among various flame retardant systems, nanocarbon materials (such as fullerenes, carbon nanotubes and graphene) have gradually become a hot topic of research as a halogen-free, heat-resistant, green and environmentally friendly flame retardant material. Among them, carbon quantum dots, as an emerging nanocarbon material with an average diameter of less than 10 nm, have shown potential application prospects in the field of flame retardants due to their good biocompatibility and physicochemical properties. So far, some work has reported the application of carbon quantum dots in the field of flame retardancy: (1) Professor Niu Mei's team reported in Cellulose 2022, 29, 9469–9486 that biomass carbon dots (CDs) particles were interspersed in an ammonium polyphosphate (APP) layer, and a new type of efficient CDs-based APP (CDs-APP) composite flame retardant was realized through integration technology, and it was coated on cotton fibers to improve the flame retardant properties. (2) Professor Wang Rui's team reported in the journal Polymer Degradation and Stability 2021, 109766 that gelatin-based carbon dots were prepared using a simple one-step hydrothermal method using biomaterial gelatin as raw material, and were integrated into the PET molecular chain through copolymerization. The limiting oxygen index reached 29%, the peak heat release was reduced by 42.66%, and the total smoke content was reduced by 62.64%, showing good flame retardant effect. (3) Professor Chen Su's team reported in the Journal of Materials Science & Technology 2021, 06, 056 that carbon quantum dots were prepared using polypropylene carbonate (PPC) and ethylenediamine as raw materials, and demonstrated their application as "ink" for printing highly fluorescent patterns and as a green flame retardant for highly flammable materials.

[0004] The above-listed research reports show that although carbon quantum dots with certain flame retardant properties can be prepared, they often need to be used in conjunction with conventional flame retardants to achieve better flame retardant effects. In addition, carbon quantum dots are applied to various fiber substrates in a post-processing manner, and their bonding strength with the fiber substrate is poor. Therefore, it is urgent to develop a carbon quantum dot that has a flame retardant effect and is well bonded to the fiber substrate. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a preparation method and application of nitrogen-phosphorus-silicon co-doped flame retardant fluorescent carbon quantum dots. On the premise of maintaining the good fluorescence properties of carbon quantum dots, a nitrogen-phosphorus-silicon co-doping synthesis method is provided to prepare new nitrogen-phosphorus-silicon co-doped carbon quantum dots with excellent fluorescence properties and flame retardant properties, and they are well combined with fiber substrates, providing new possibilities for the application of carbon quantum dots in the flame retardant field and the fiber field.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: One of the purposes of the present invention is to provide a nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots, the characteristics of the carbon quantum dots are: good monodispersity, a particle size range of 2-8 nm, and a fluorescence yield of 11-18%.

[0007] The second object of the present invention is to provide a method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots, the preparation method comprising the following steps: S1. Preparation of phosphorus source compound Add pentaerythritol to an appropriate amount of tetrahydrofuran, stir evenly and heat to 40-50°C, add catalyst triethylamine, continue to drop phosphorus oxychloride and react for 90-120min, then heat to 60-80°C and react for 2-3h, then heat to 100-110°C for 60-90min to complete the reaction, filter and dry to obtain spirocyclic phosphate dichloride.

[0008] Preferably, the molar ratio of pentaerythritol to phosphorus oxychloride is 1:2.5-4.

[0009] Preferably, the catalyst triethylamine is added in an amount of 1 to 2% of the mass of pentaerythritol.

[0010] Preferably, the dropping rate of the phosphorus oxychloride is 8-15 ml / min.

[0011] S2. Preparation of nitrogen-silicon co-doped carbon quantum dots S21: mixing and dissolving the carbon source compound and the nitrogen source compound in deionized water, and uniformly dispersing by ultrasonication to obtain a mixed solution A; S22: adding the silanization agent dropwise into the mixed solution A, and mixing by ultrasonication to obtain a mixed solution B; S23: The mixed solution B is transferred to a reactor, and subjected to a hydrothermal reaction at 160-220° C. for 4-10 hours. The nitrogen-silicon co-doped carbon quantum dots are obtained by suction filtration, purification, and washing with deionized water.

[0012] Preferably, the mass ratio of the carbon source compound to the nitrogen source compound in the mixed solution A is 1:0.2-2; the mass ratio of the carbon source compound to deionized water is 1:10-100.

[0013] Preferably, the carbon source compound is one or more organic acids such as citric acid, tartaric acid, oxalic acid, etc.

[0014] Preferably, the nitrogen source compound is one or more organic amines such as melamine, dicyandiamide, aromatic amine and polyethyleneimine.

[0015] Preferably, the mass ratio of the carbon source compound to the silanization agent in the mixed solution B is 1:0.5-4.

[0016] Preferably, the silanization agent is one or more aminosilanes such as 3-aminopropyltrimethoxysilane and γ-aminopropyltrimethoxysilane.

[0017] S3. Preparation of nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots The spirocyclic phosphate dichloride was dissolved in DMF, and nitrogen-silicon co-doped carbon quantum dots and stabilizer were added. After mixing evenly, the temperature was raised to 40-50°C for reaction for 3-5 hours. After the reaction, the temperature was lowered to room temperature. After filtration, ether washing and drying, nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots were obtained.

[0018] Preferably, the mass ratio of the nitrogen-silicon co-doped carbon quantum dots to the spirocyclic phosphate dichloride is 6 to 9:1.

[0019] Preferably, the stabilizer is N,N-dimethylaniline, and the added amount is 25-35% of the mass of the spirocyclic phosphate dichloride.

[0020] The working principle of this preparation method is mainly that, in the hydrothermal synthesis process, by adding carbon source compounds, nitrogen source compounds and silanization agents, nitrogen and silicon elements are added during the formation of carbon quantum dots to prepare nitrogen-silicon co-doped carbon quantum dots. At the same time, the surface of the carbon quantum dots contains abundant amino groups, in which one hydrogen atom in the amino group is replaced by the phosphorus source compound spirocyclic phosphate dichloride to obtain nitrogen-phosphorus-silicon co-doped carbon quantum dots. Nitrogen, phosphorus and silicon elements can improve the fluorescence yield and flame retardant properties of carbon quantum dots. At the same time, the surface of the carbon quantum dots contains a spirocyclic structure with good rigidity and strong thermal stability, which can be further applied to fiber substrates to improve their thermal stability and mechanical properties. Moreover, these three elements are doped into the carbon quantum dots at the same time, and their flame retardant properties can be significantly improved through the synergistic effect of multiple elements.

[0021] The third purpose of the present invention is to provide an application of nitrogen-phosphorus-silicon co-doped flame retardant fluorescent carbon quantum dots, which is to add nitrogen-phosphorus-silicon co-doped flame retardant fluorescent carbon quantum dots and a photoinitiator into anhydrous ethanol, stir evenly, spray them onto the surface of the fabric, and treat them with UV light to obtain a modified fabric with flame retardant properties.

[0022] Preferably, the mass ratio of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots, the photoinitiator and anhydrous ethanol is 12-16:0.5-1:60-70.

[0023] Preferably, the photoinitiator is one or more of a diaryl iodonium salt and a triaryl sulfonium salt.

[0024] Due to the adoption of the above technical solution, the technical effects achieved by the present invention are: 1. The nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots prepared by the present invention have good monodispersity and uniform particle size. At the same time, the carbon quantum dots contain nitrogen, phosphorus and silicon elements and have excellent fluorescence properties and flame retardant properties.

[0025] 2. The preparation method of nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots provided by the present invention is simple and easy, does not require complicated experimental conditions, and has the characteristics of being non-toxic, easy to synthesize, and environmentally friendly.

[0026] 3. The nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots prepared by the present invention have a spirocyclic structure on their surface, which is sprayed on the fabric surface in a finishing form. Under the action of photoinitiator and UV light, the ring is opened and cross-linked, and they can be effectively combined with the fiber substrate, thus solving the problem of shedding during subsequent washing and use.

[0027] 4. The nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots prepared by the present invention, as an emerging carbon material, maintain the good fluorescence properties of carbon quantum dots and also have excellent flame retardant properties. Therefore, they have broad application prospects in the fields of green and environmentally friendly flame retardancy and fluorescence detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a TEM characterization image of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots synthesized in Example 4. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments.

[0030] Embodiment 1: A method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots and its application, the method comprising the following steps: S1. Preparation of phosphorus source compound Add pentaerythritol to an appropriate amount of tetrahydrofuran, stir evenly and heat to 45°C, add catalyst triethylamine, continue to drop phosphorus oxychloride and react for 110 minutes, then heat to 70°C and react for 2.5 hours, then heat to 105°C for 80 minutes to complete the reaction, filter and dry to obtain spirocyclic phosphate dichloride.

[0031] The molar ratio of pentaerythritol to phosphorus oxychloride is 1:3.2.

[0032] The added amount of the catalyst triethylamine is 1.5% of the mass of pentaerythritol.

[0033] The dropping rate of the phosphorus oxychloride was 12 ml / min.

[0034] S2. Preparation of nitrogen-silicon co-doped carbon quantum dots S21: dissolving citric acid and dicyandiamide in deionized water, and uniformly dispersing by ultrasonication to obtain a mixed solution A; S22: adding 3-aminopropyltrimethoxysilane dropwise into the mixed solution A, and mixing by ultrasonication to obtain a mixed solution B; S23: The mixed solution B is transferred to a reactor and subjected to a hydrothermal reaction at 200° C. for 6 h. The nitrogen-silicon co-doped carbon quantum dots are obtained after filtration, purification, and washing with deionized water.

[0035] The mass ratio of citric acid to dicyandiamide in the mixed solution A is 1:0.5; the mass ratio of citric acid to deionized water is 1:20.

[0036] The mass ratio of citric acid to 3-aminopropyltrimethoxysilane in the mixed solution B is 1:1.5.

[0037] S3. Preparation of nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots The spirocyclic phosphate dichloride was dissolved in DMF, and then nitrogen-silicon co-doped carbon quantum dots and stabilizer were added. After mixing evenly, the temperature was raised to 45°C for reaction for 4 hours. After the reaction was completed, the temperature was lowered to room temperature. After filtration, ether washing and drying, nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots were obtained.

[0038] The mass ratio of the nitrogen-silicon co-doped carbon quantum dots to the spirocyclic phosphate dichloride is 7:1.

[0039] The stabilizer is N,N-dimethylaniline, and the added amount is 29% of the mass of the spirocyclic phosphate dichloride.

[0040] S4. Application Flame-retardant fluorescent carbon quantum dots co-doped with nitrogen-phosphorus-silicon and diaryl iodonium salt are added into anhydrous ethanol and stirred evenly, then sprayed onto the surface of cotton fabric and irradiated with UV light to obtain modified fabric with flame-retardant properties.

[0041] The mass ratio of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots, diaryl iodonium salt and anhydrous ethanol is 14:0.8:65.

[0042] The spraying amount is 400g / m 2 , the wavelength of the UV light is 365nm.

[0043] The particle size range of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots prepared in Example 1 is 4 to 7 nm, and the fluorescence yield is 16%. They are sprayed on the surface of cotton fabric and the flame retardant properties of the modified cotton fabric are tested. The LOI value is measured to be 30.6%, and the flame retardant performance loss rate is 1.2% after washing 50 times.

[0044] Example 2: A method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots and its application, the method comprising the following steps: S1. Preparation of phosphorus source compound Add pentaerythritol to an appropriate amount of tetrahydrofuran, stir evenly and heat to 40°C, add catalyst triethylamine, continue to drop phosphorus oxychloride and react for 90 minutes, then heat to 60°C and react for 3 hours, then heat to 100°C for 60 minutes to complete the reaction, filter and dry to obtain spirocyclic phosphate dichloride.

[0045] The molar ratio of pentaerythritol to phosphorus oxychloride is 1:2.5.

[0046] The added amount of the catalyst triethylamine is 1% of the mass of pentaerythritol.

[0047] The dropping rate of the phosphorus oxychloride is 8 ml / min.

[0048] S2. Preparation of nitrogen-silicon co-doped carbon quantum dots S21: dissolving citric acid and dicyandiamide in deionized water, and uniformly dispersing by ultrasonication to obtain a mixed solution A; S22: adding 3-aminopropyltrimethoxysilane dropwise into the mixed solution A, and mixing by ultrasonication to obtain a mixed solution B; S23: The mixed solution B is transferred to a reactor, and subjected to a hydrothermal reaction at 160° C. for 10 h. The nitrogen-silicon co-doped carbon quantum dots are obtained by suction filtration, purification, and washing with deionized water.

[0049] The mass ratio of citric acid to dicyandiamide in the mixed solution A is 1:0.2; the mass ratio of citric acid to deionized water is 1:10.

[0050] The mass ratio of citric acid to 3-aminopropyltrimethoxysilane in the mixed solution B is 1:0.5.

[0051] S3. Preparation of nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots The spirocyclic phosphate dichloride was dissolved in DMF, and then nitrogen-silicon co-doped carbon quantum dots and stabilizer were added. After mixing evenly, the temperature was raised to 40°C for reaction for 3 hours. After the reaction, the temperature was lowered to room temperature. After filtration, ether washing and drying, nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots were obtained.

[0052] The mass ratio of the nitrogen-silicon co-doped carbon quantum dots to the spirocyclic phosphate dichloride is 9:1.

[0053] The stabilizer is N,N-dimethylaniline, and the added amount is 25% of the mass of the spirocyclic phosphate dichloride.

[0054] S4. Application Flame-retardant fluorescent carbon quantum dots co-doped with nitrogen, phosphorus and silicon and diaryl iodonium salt are added into anhydrous ethanol and stirred evenly, then sprayed onto the surface of fabric and treated with UV light to obtain modified fabric with flame-retardant properties.

[0055] The mass ratio of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots, diaryl iodonium salt and anhydrous ethanol is 12-16:0.5-1:60-70.

[0056] The spraying amount is 400g / m 2 , the wavelength of the UV light is 365nm.

[0057] The particle size range of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots prepared in Example 2 is 4 to 7 nm, and the fluorescence yield is 11%; they are sprayed on the surface of cotton fabric and the flame retardant properties of the modified cotton fabric are tested. The LOI value is measured to be 28.8%, and the flame retardant performance loss rate is 3.5% after washing 50 times.

[0058] Example 3: A method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots and its application, the method comprising the following steps: S1. Preparation of phosphorus source compound Add pentaerythritol to an appropriate amount of tetrahydrofuran, stir evenly and heat to 50°C, add catalyst triethylamine, continue to drop phosphorus oxychloride and react for 120 minutes, then heat to 80°C and react for 2 hours, then heat to 110°C for 90 minutes to complete the reaction, filter and dry to obtain spirocyclic phosphate dichloride.

[0059] The molar ratio of pentaerythritol to phosphorus oxychloride is 1:4.

[0060] The added amount of the catalyst triethylamine is 2% of the mass of pentaerythritol.

[0061] The dropping rate of the phosphorus oxychloride is 15 ml / min.

[0062] S2. Preparation of nitrogen-silicon co-doped carbon quantum dots S21: dissolving citric acid and polyethyleneimine in deionized water, and uniformly dispersing by ultrasonication to obtain a mixed solution A; S22: adding 3-aminopropyltrimethoxysilane dropwise into the mixed solution A, and mixing by ultrasonication to obtain a mixed solution B; S23: The mixed solution B is transferred to a reactor and subjected to a hydrothermal reaction at 220° C. for 4 h. The nitrogen-silicon co-doped carbon quantum dots are obtained after filtration, purification, and washing with deionized water.

[0063] The mass ratio of citric acid to polyethyleneimine in the mixed solution A is 1:2; the mass ratio of citric acid to deionized water is 1:100.

[0064] The mass ratio of citric acid to 3-aminopropyltrimethoxysilane in the mixed solution B is 1:4.

[0065] S3. Preparation of nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots The spirocyclic phosphate dichloride was dissolved in DMF, and then nitrogen-silicon co-doped carbon quantum dots and stabilizer were added. After mixing evenly, the temperature was raised to 50°C for reaction for 5 hours. After the reaction was completed, the temperature was lowered to room temperature. After filtration, ether washing and drying, nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots were obtained.

[0066] The mass ratio of the nitrogen-silicon co-doped carbon quantum dots to the spirocyclic phosphate dichloride is 6:1.

[0067] The stabilizer is N,N-dimethylaniline, and the added amount is 35% of the mass of the spirocyclic phosphate dichloride.

[0068] S4. Application Flame-retardant fluorescent carbon quantum dots co-doped with nitrogen, phosphorus and silicon and diaryl iodonium salt are added into anhydrous ethanol and stirred evenly, then sprayed onto the surface of fabric and treated with UV light to obtain modified fabric with flame-retardant properties.

[0069] The mass ratio of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots, diaryl iodonium salt and anhydrous ethanol is 16:1:70.

[0070] The spraying amount is 400g / m 2 , the wavelength of the UV light is 365nm.

[0071] The particle size range of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots prepared in Example 3 is 4 to 8 nm, and the fluorescence yield is 18%; they are sprayed on the surface of cotton fabric and the flame retardant properties of the modified cotton fabric are tested. The LOI value is measured to be 31.2%, and the flame retardant performance loss rate is 1.6% after washing 50 times.

[0072] Example 4: The difference between this example and Example 2 is that citric acid is replaced by tartaric acid, and the rest is consistent with Example 4. The particle size range of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots prepared in Example 4 is 2 to 6 nm, and the fluorescence yield is 12%; it is sprayed on the surface of cotton fabric and the flame retardant properties of the modified cotton fabric are tested. The LOI value is measured to be 28.5%, and the flame retardant performance loss rate after washing 50 times is 3.1%.

[0073] Comparative Example 1: The flame retardant properties of the cotton fabric were directly tested without flame retardant treatment. The results were as follows: the LOI value was 18.2%.

[0074] Comparative Example 2: Dissolve citric acid in 20 times deionized water and disperse it evenly by ultrasonication to obtain a mixed solution A. Transfer the mixed solution A to a reactor and perform a hydrothermal reaction at 180°C for 6 hours. After filtration, purification and washing, carbon quantum dots without doping with other elements are obtained. The particle size of the prepared carbon quantum dots is 2 to 8 nm, and the fluorescence yield is 8%.

[0075] Comparative Example 3: S1, citric acid, dicyandiamide and phytic acid were mixed and dissolved in deionized water, and ultrasonically dispersed to obtain a mixed solution A; S2, adding 3-aminopropyltrimethoxysilane dropwise into the mixed solution A, and mixing evenly by ultrasonication to obtain a mixed solution B; S3, transferring the mixed solution B to a reactor, performing a hydrothermal reaction at 200° C. for 6 hours, and obtaining nitrogen-phosphorus-silicon co-doped carbon quantum dots through suction filtration, purification, and washing; The mass ratio of citric acid, dicyandiamide and phytic acid in the mixed solution A is 1:0.5:0.5; the mass ratio of citric acid to deionized water is 1:20.

[0076] The mass ratio of citric acid to 3-aminopropyltrimethoxysilane in the mixed solution B is 1:1.5; S4, adding nitrogen-phosphorus-silicon co-doped carbon quantum dots and diaryl iodonium salt into anhydrous ethanol and stirring evenly, spraying them onto the surface of cotton fabric, and irradiating them with UV light to obtain a modified fabric with flame retardant properties; The mass ratio of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots, diaryliodonium salt and anhydrous ethanol is 14:0.8:65; The spraying amount is 400g / m 2 , the wavelength of the UV light is 365nm.

[0077] The particle size of the nitrogen-phosphorus-silicon co-doped carbon quantum dots prepared in Comparative Example 3 is 3 to 6 nm, and the fluorescence yield is 10%. They are sprayed on the surface of cotton fabric to test the flame retardant properties of the modified cotton fabric. The LOI value is 24.3%, and the flame retardant performance loss rate after 50 washings is 18.7%; the flame retardant loss rate after washing is relatively large. This is because the nitrogen-phosphorus-silicon co-doped carbon quantum dots in Comparative Example 3 have no spirocyclic structure and cannot be open-ring cross-linked, so the bonding strength with the fabric is poor, which is manifested as a significant decrease in the flame retardant effect after washing.

[0078] Figure 1 This is a TEM characterization image of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots synthesized in Example 4 (the inset is a TEM image at a high magnification). The particle size of the carbon quantum dots is between 2 and 6 nm, and a clear lattice can be observed, which is consistent with the structural characteristics of graphite carbon.

[0079] Unless otherwise specified, the ratios and percentages described in the present invention are all weight ratios and weight percentages; and the raw materials are all commercially available.

[0080] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots, characterized in that: The preparation method comprises the preparation of phosphorus source compounds, the preparation of nitrogen-silicon co-doped carbon quantum dots and the preparation of nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots.

2. The method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots according to claim 1, characterized in that: The preparation of the phosphorus source compound is as follows: pentaerythritol is added to an appropriate amount of tetrahydrofuran, stirred evenly and heated to 40-50° C., a catalyst triethylamine is added, phosphorus oxychloride is continuously added dropwise and reacted for 90-120 minutes, then the temperature is raised to 60-80° C. and reacted for 2-3 hours, then the temperature is raised to 100-110° C. for 60-90 minutes to complete the reaction, and the spirocyclic phosphate dichloride is obtained by suction filtration and drying.

3. The method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots according to claim 2, characterized in that: The molar ratio of pentaerythritol to phosphorus oxychloride is 1:2.5-4; The catalyst triethylamine is added in an amount of 1 to 2% of the mass of pentaerythritol; The dropping rate of the phosphorus oxychloride is 8-15 ml / min.

4. The method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots according to claim 1, characterized in that: The preparation of nitrogen-silicon co-doped carbon quantum dots comprises the following steps: S21: mixing and dissolving the carbon source compound and the nitrogen source compound in deionized water, and uniformly dispersing by ultrasonication to obtain a mixed solution A; S22: adding the silanization agent dropwise into the mixed solution A, and mixing by ultrasonication to obtain a mixed solution B; S23: The mixed solution B is transferred to a reactor, and subjected to a hydrothermal reaction at 160-220° C. for 4-10 hours. The nitrogen-silicon co-doped carbon quantum dots are obtained by suction filtration, purification, and washing with deionized water.

5. The method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots according to claim 4, characterized in that: The mass ratio of the carbon source compound to the nitrogen source compound in the mixed solution A is 1:0.2-2; the mass ratio of the carbon source compound to deionized water is 1:10-100.

6. The method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots according to claim 4, characterized in that: The carbon source compound is one or more of citric acid, tartaric acid, and oxalic acid; The nitrogen source compound is one or more of melamine, dicyandiamide, aromatic amine and polyethyleneimine; The mass ratio of the carbon source compound to the silanization agent in the mixed solution B is 1: 0.5-4; The silanization agent is one or more of 3-aminopropyltrimethoxysilane and γ-aminopropyltrimethoxysilane.

7. The method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots according to claim 1, characterized in that: The method for preparing the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots is as follows: dissolving spirocyclic phosphate dichloride in DMF, adding nitrogen-silicon co-doped carbon quantum dots and a stabilizer, mixing evenly, heating to 40-50° C. for reaction for 3-5 hours, cooling to room temperature after the reaction is completed, filtering, washing with ether, and drying to obtain the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots.

8. The method for preparing nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots according to claim 7, characterized in that: The mass ratio of the nitrogen-silicon co-doped carbon quantum dots to the spirocyclic phosphate diacyl chloride is 6 to 9:1; The stabilizer is N,N-dimethylaniline, and the added amount is 25-35% of the mass of the spirocyclic phosphate diacyl chloride.

9. An application of nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots, characterized in that: The application method comprises the following steps: adding nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots and a photoinitiator into anhydrous ethanol, stirring the mixture evenly, spraying the mixture onto the surface of the fabric, and subjecting the mixture to UV light irradiation treatment to obtain a modified fabric with flame-retardant properties.

10. The use of nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots according to claim 9, characterized in that: The mass ratio of the nitrogen-phosphorus-silicon co-doped flame-retardant fluorescent carbon quantum dots, the photoinitiator and the anhydrous ethanol is 12-16:0.5-1:60-70; The photoinitiator is one or more of diaryliodonium salt and triarylsulfonium salt.

Citation Information

Patent Citations

  • Carbon quantum dot-polymer composite material, and preparation method and application thereof

    CN110819097A

  • Carbon quantum dot co-doped by silicon and nitrogen and preparation method and application thereof

    CN110938430A

  • Flame-retardant luminous formaldehyde-reducing functional aid as well as preparation method and application thereof

    CN113249056A

  • Fluorescent carbon quantum dot and synthesis method and application of nitrogen-phosphorus co-doped fluorescent carbon quantum dot

    CN114620710A

  • Carbon dot fluorescent nanomaterial with controllable energy level and synthesis method

    CN115044365A